The roles of plasticity versus dominance in maintaining polymorphism in mating strategies. Issue 1 (December 2017) - Moulherat, Sylvain; Chaine, Alexis; Mangin, Alain; Aubret, Fabien; Sinervo, Barry; Clobert, Jean
Abstract Although natural selection is expected to reduce variability, polymorphism is common in nature even under strong selective regimes. Discrete polymorphisms in mating strategies are widespread and offer a good opportunity to understand the genetic processes that allow the maintenance of polymorphism in relatively simple systems. Here we explored the genetic mechanism underlying the expression of discrete mating strategies in the rock-paper-scissors (RPS) game. Heterozygotes carry the genetic information for two different strategies, yet little attention has been devoted to the mechanisms underpinning heterozygote phenotype and its consequences for allele frequency dynamics. We explored the maintenance of polymorphism under 1) genetic dominance or 2) plasticity, as mechanisms driving the expression of alternative strategies in males. We developed an alternative mating strategy model and analysed allele frequency dynamics using time series analyses. Our results show that both genetic mechanisms can maintain polymorphism depending on population demographic characteristics but that plasticity can enhance the likelihood that polymorphism is maintained relative to dominance. Time series analysis on simulation outcomes show that the RPS game is mostly driven by a single strategy, but the importance of this strategy on long term dynamics is stronger when gene expression shows dominance rather than plasticity.